Sperm and embryo analysis in a carrier of supernumerary inv dup(15) marker chromosome - Oracova, Eva; Musilova, Petra; Kopecna, Olga; Rybar, Roman; Vozdova, Miluse; Vesela, Katerina; Rubes, Jiri (Journal of andrology, 2009)
We identified a small, paternally inherited, supernumerary marker chromosome, inv dup(15), in a phenotypically normal and normozoospermic male from a couple with reproductive problems. Sperm analysis by fluorescence in situ hybridization (FISH) showed that the marker was present in 26% of sperm nuclei. The disomy 15 was 10 times higher than in normal control donors. FISH analysis for aneuploidies of the other chromosomes showed an increase in nondisjunction of chromosome 21. We also examined 24 embryos by preimplantation genetic diagnosis, and 10 embryos (41.7%) contained the marker. This report provides information about inheritance of inv dup(15) from a male carrier.
Keywords: heterozygot; embryo savčí; Male; Pedigree; rodokmen; Heterozygote; lidské chromozomy, pár 15; hybridizace in situ fluorescenční; Infertility, Male; Pregnancy; těhotenství; Adult; Spermatozoa; Embryo, Mammalian; dospělí; mužské pohlaví; Chromosomes, Human, Pair 15; lidé; ženské pohlaví; Humans; uniparentální disomie; spermie; In Situ Hybridization, Fluorescence; Female; Uniparental Disomy; mužská infertilita